2016
DOI: 10.2527/jas.2015-9836
|View full text |Cite
|
Sign up to set email alerts
|

The effect of porcine reproductive and respiratory syndrome virus and porcine epidemic diarrhea virus challenge on growing pigs II: Intestinal integrity and function1

Abstract: The objective of this study was to determine if intestinal function and integrity is altered due to porcine reproductive and respiratory syndrome (PRRS) virus and porcine epidemic diarrhea (PED) virus infection in growing pigs. Forty-two gilts (16.8 ± 0.6 kg BW), naïve for PRRS and PED, were selected and randomly assigned to 1 of 4 treatments: 1) a control (CON; = 6), 2) PRRS virus challenge only (PRRS; = 12), 3) PED virus challenge only (; = 12), or 4) coinfection of PRRS + PED viruses (PRP; = 12). Treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 35 publications
5
26
0
Order By: Relevance
“…Previous work reported that PEDV detected by IHC is most abundant at dpi 5 and this coincides with increased crypt stem cell proliferation, DNA fragmentation, and active glutamine transport in the jejunum ( Curry et al, 2017b ). In agreement with this study, it has been well characterized that during peak infection PEDV reduces VH ( Stevenson et al, 2013 ; Madson et al, 2014 ) and that PEDV increases villus fusion as well as immune cell infiltrates ( Schweer et al, 2015a ). Crypt stem cell proliferation has been assessed using Ki67 IHC, and PEDV-inoculated pigs have been shown to have increased Ki67-positive cells in small intestinal crypts ( Jung et al, 2015 ; Curry et al, 2017b ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous work reported that PEDV detected by IHC is most abundant at dpi 5 and this coincides with increased crypt stem cell proliferation, DNA fragmentation, and active glutamine transport in the jejunum ( Curry et al, 2017b ). In agreement with this study, it has been well characterized that during peak infection PEDV reduces VH ( Stevenson et al, 2013 ; Madson et al, 2014 ) and that PEDV increases villus fusion as well as immune cell infiltrates ( Schweer et al, 2015a ). Crypt stem cell proliferation has been assessed using Ki67 IHC, and PEDV-inoculated pigs have been shown to have increased Ki67-positive cells in small intestinal crypts ( Jung et al, 2015 ; Curry et al, 2017b ).…”
Section: Discussionsupporting
confidence: 90%
“…Total RNA was isolated from LD muscle as previously described ( Schweer et al, 2015a ). Total protein was set relative to total RNA to assess protein synthesis efficiency, which has previously been published ( Pringle et al, 1993 ).…”
Section: Methodsmentioning
confidence: 99%
“…Adverse health events and the accompanying hypophagia results in economically significant losses in pig growth performance worldwide. However, it is unclear how an adverse health event such as PRRSV challenge directly, or indirectly via hypophagia, impacts small intestinal function and integrity [8]. Moreover, little is known about how much disease hypophagia contributes to attenuated pig performance and modulations in small intestinal function and integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in intestinal integrity and function have been documented under a variety of stressors, including heat stress [3,4], weaning stress [5,6], and enteric disease challenges such as with Porcine Epidemic Diarrhea Virus [PEDV; 7,8,9]. However, reduced nutrient intake is often reported in accompaniment of these stressors, which alone can modulate intestinal integrity and function [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The long‐term impact of PEDV and potentially PDCoV on performance may be due to the systemic inflammatory effects on feed intake and utilization, localized effects on enterocyte health and function, or a combination of the two. For example, infection with PEDV results in apoptosis of epithelial cells, increased gastrointestinal permeability, disruption of tight and adherens junctions of enterocytes, and reduced goblet cells present in the small intestine (Jung, Eyerly, Annamalai, Lu, & Saif, ; Jung & Saif, ; Kim & Lee, ; Schweer, Pearce et al., ). These disruptions to normal gastrointestinal anatomy and physiology likely impact digestive capacity and function.…”
Section: Long‐term Impact Of Secd On Pig Growth and Productionmentioning
confidence: 99%